Cost analysis of an outbreak of Clostridium difficile infection ribotype 027 in a Dutch tertiary care centre. Issue 4 (April 2017) - van Beurden, Y.H.; Bomers, M.K.; van der Werff, S.D.; Pompe, E.A.P.M.; Spiering, S.; Vandenbroucke-Grauls, C.M.J.E.; Mulder, C.J.J.
Summary: Background: The economic impact of Clostridium difficile infection (CDI) on the healthcare system is significant. From May 2013 to May 2014, an outbreak of C. difficile ribotype 027 occurred in a Dutch tertiary care hospital, involving 72 patients. The primary aim of this study was to provide insight into the financial burden that this CDI outbreak brought upon this hospital. Methods: A retrospective analysis was performed to estimate the costs of a one-year-long C. difficile ribotype 027 outbreak. Medical charts were reviewed for patient data. In addition, all costs associated with the outbreak control measures were collected. Findings: The attributable costs of the whole outbreak were estimated to be €1, 222, 376. The main contributing factor was missed revenue due to increased length of stay of CDI patients and closure of beds to enable contact isolation of CDI patients (36%). A second important cost component was extra surveillance and activities of the Department of Medical Microbiology and Infection Control (25%). Conclusion: To the authors' knowledge, this is the first study to provide insight into the attributable costs of CDI in an outbreak setting, and to delineate the major cost items. It is clear that the economic consequences of CDI are significant. The high costs associated with a CDI outbreak should help to justify the use of additional resources for CDI prevention and control.